The Car book : The definitive visual history - Hennessy, Kathryn; Hester, Beth Landis; DK Publishing, Inc. (New York, N.Y. : DK Pub., 2011)
Traces the history of the automobile, from technological developments and manufacturers to the changing cultural backdrop of various models, and features photographs of the most noted cars of each decade.
First automobiles up to 1920 -- The 1920s -- The 1930s -- The 1940s -- The 1950s -- The 1960s -- The 1970s -- The 1980s -- The 1990s -- 2000 onward.
Includes index.
Two cards in back pocket.
Keywords: Automobiles -- Pictorial works; Automobiles -- History -- Chronology; Automobiles -- Pictorial works; Automobiles -- History